Association between dental caries, odontogenic infections, oral hygiene status and anthropometric measurements of children in Lagos, Nigeria - Afolabi Oyapero; Aderinsola Adenaike; Augustine Edomwonyi; Abiola Adeniyi; Olubukola Olatosi (Universidade Estadual de Campinas, 2021)
Dental caries is a significant public health problem afflicting about a third of the world's population which impacts nutrition, quality of life and systemic health. Aim: We explored associations between dental caries, odontogenic infections, oral hygiene and anthropometric measurements of children in Lagos, Nigeria. Methods: A pretested validated questionnaire was administered on 278 children who also received anthropometric assessment and dental examinations. Caries was scored according to WHO criteria and untreated dental caries by the Pulpal Exposure, Ulceration, Fistula, Abcess (PUFA/pufa) index. The weight for age (WAZ), height for age (HAZ), and weight for height (WHZ) parameters evaluated nutritional status. Categorical and continuous data were analysed by χ2-test and ANOVA. Regression analysis was done and statistical significance set at p ≤ 0.05. Results: The prevalence of Decayed, Missing, and Filled Teeth (DMFT + dmft) > 0 was 220 (79.1%) and the proportion of d+D teeth in dmft+DMFT index was 194 (70.0%). The prevalence of odontogenic infections due to caries (PUFA + pufa > 0) was 172 (61.8%). 74 (26.6%) children were stunted; 12 (4.3%) were underweight while 30 (10.8%) were wasted. Children with PUFA + pufa > 1 had increased risk of wasting (OR: 2.45; 95% CI: 1.16-4.88). Children with DMFT+dmft >5 were also significantly underweight with odds ratios of 2.34 (95% CI 1.04-4.33). Conclusions: There was significant association between untreated dental caries, odontogenic infections and stunting, wasting and being underweight among the children studied. Policy makers should be aware of the additional burden that oral neglect has on anthropometric indices.